ASPECTOS GERAIS DA QUíMICA DOS DITIOCARBAMATOS E DE SEUS COMPLEXOS METáLICOS E INTERAçõES DESSAS ESPéCIES QUíMICAS COM IMPORTANTES ENZIMAS – UMA BREVE REVISãO - Daniele C. Menezes; Geraldo M. de Lima (Química Nova, 2021)
GENERAL ASPECTS OF THE CHEMISTRY OF DITHIOCARBAMATES, THEIR METALLIC COMPLEXES AND THEIR INTERACTIONS WITH IMPORTANTE ENZYMES – A BRIEF REVISION. Dithiocarbamates (DTCs) comprise a series of compounds included in the class of 1,1`dithiolates. The application of these organic molecules in the coordination chemistry of some metals is well explored in the last decades, along with their potential applications in medicinal chemistry. In view of our expertise in this field, the syntheses of new DTCS, their coordination chemistry towards various metallic cations and their biocide activities, we summarize in this manuscript the outcomes of some investigations registered in the literature, involving the interactions of DTCs or their complexes with some key enzymes such as carbonic anhydrases, superoxide dismutase, urease, tyrosinase, glutathione, caspases and dehydrogenases. It is provided with a brief introduction of the chemistry of DTCs, electrochemistry, the kinetics of formation, solubility and stability towards solvation. The next topics summarize the results of some experiments concerning the inhibition of these cited enzymes effected by DTCs and some of their coordination complexes. The final remarks and conclusion of the outcomes are provided at the end of the manuscript.